Comparative Plasma Endocrine, Metabolic and Mineral Profile of Cyclic, Acyclic, Endometritic and Pregnant Buffaloes - Patel, Binal R; Panchal, MT; Dhami, AJ; Sarvaiya, NP; Pathan, MM (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Circulating concentrations of hormones, metabolites, and minerals reflect the physio-pathological status of reproduction in animals. This study was carried out on infertile (anestrus, endometritic), normal healthy cyclic and pregnant buffaloes to evaluate the comparative plasma progesterone (P4) and estrogen (E2) hormones, plasma total protein, total cholesterol, calcium, and phosphorus profile. The study showed higher mean plasma E2 and lower P4 levels in the follicular phase of estrous cycle in buffaloes. Significantly (p <0.05) higher mean plasma P4 level and lower E2 levels were recorded during the luteal phase and in endometritic and pregnant buffaloes. Total plasma protein concentration was non-significantly higher in normal cyclic than acyclic and endometritic buffaloes. It was also comparatively lower in buffalo with 9 months of pregnancy than 3 and 6 months of pregnancy. The mean plasma total cholesterol level was significantly (p<0.05) higher in pregnant than acyclic and endometritic buffaloes. Cyclic buffaloes had significantly (p <0.05) higher mean plasma calcium levels than acyclic buffaloes. Plasma phosphorus concentration, however, did not show any significant difference between different stages of the reproductive cycle.